Identifying and disentangling the impact of fiscal decentralization on economic growth - Gustavo Canavire-Bacarreza; Jorge Martinez-Vazquez; Bauyrzhan Yedgenov (Inter-American Development Bank (IDB), 2019)
This paper revisits the relationship between fiscal decentralization and economic growth by addressing the endogeneity issue stemming from reverse causality and unobserved factors that has plagued previous extensive literature on this subject. In our approach, we use the Geographic Fragmentation Index (GFI) and country size as instrumental variables, which we argue are strong and consistent instruments for fiscal decentralization. Empirically, we find that indeed both instruments are strong and valid in the first stage of estimation and that on average, a 10 percent increase in subnational expenditure or revenue shares - the conventional measures of decentralization - will increase GDP per capita growth by approximately 0.4 percentage points; however, the results differ for developed versus developing countries.
Keywords: O47; H77; E62; 330; Fiscal Decentralization; Geography; Geographic Fragmentation Index; Economic Growth